Pengaruh Kualitas Produk, Potongan Harga Dan Penggunaan Instagram Terhadap Keputusan Pembelian di Juragansapi.com - Hermansyah, Hermansyah; Regita, Imla (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to find out how much influence product quality, discounts, and use of Instagram have on purchasing decisions at Juragansapi.com. The population in this research is all consumers who buy products at Juragansapi.com. Sampling in this research used Hair.et.al theory to obtain a sample of 190 respondents. The research method used is a quantitative approach with an associative type of research. The data analysis techniques used are descriptive analysis, instrument test, classical assumption test, multiple linear regression analysis, t test, f test, coefficient of determination test with the SPSS version 26 program. The results of the study show that there is a partially significant influence between product quality (X1) on purchasing decisions (Y) of 44.9%, there is a partial significant influence between discounts (X2) on purchasing decisions (Y) of 51.8%, and there is a partial significant effect of Instagram use (X3) on purchasing decision (Y) was 46.3%. The results of the research conducted show that simultaneously product quality (X1), price discounts (X2), and there is a partial significant influence on the use of Instagram (X3) at Juragansapi.com (Y) amounting to 63.9% and the remaining 36, 1% is influenced by other variables not examined in this research.